Infantile Spasms in Down Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The clinical characteristics, EEG abnormalities, response to therapy, and outcome of 14 patients with infantile spasms and Down syndrome were studied at the Hopital Saint Vincent de Paul, Paris (9 cases); Universita Degli Studi de Pisa, Italy (2 cases); and Hopital de La Timone, Marseille, France (3 cases).